Student participation in multidisciplinary modules from Finnish and Vietnamese elementary teachers' perspectives - Nguyen Thi Ha, Le (My University, 2024)
Enhancing student participation is a crucial objective in developing national core curricula. To achieve effective implementation, it is important to examine teachers' understanding of student participation. This thesis aims to investigate the perceptions of Finnish and Vietnamese teachers regarding different forms of student participation, using Niemi's model of four forms of student participation (Niemi et al., 2019). Additionally, the study aims to explore how these teachers enhance student participation and identify the challenges in teaching multidisciplinary modules. The research compares the perspectives of teachers in Vietnam and Finland, highlighting both similarities and differences. The study involved four Finnish teachers and four Vietnamese teachers from public elementary schools, and data was collected through semi-structured interviews. The findings reveal that all teachers provided opportunities for student participation in three different forms within multidisciplinary modules: active-joining, collaborative, and child-initiated participation. However, child-led participation was primarily observed during free play time and was not commonly observed during multidisciplinary lessons. It is worth noting that the differences observed between the two teacher groups relate to the stage at which teachers allow students to make decisions, the areas in which students can exercise autonomy, and the influence of power dynamics within the learning environment whether within the classroom, the school, or larger communities. Furthermore, a relationship between teachers' perceptions and their practices in enhancing student participation was identified. Both Vietnamese and Finnish teachers employed a range of strategies throughout the teaching process. In general, similarities were observed in their approaches to fostering interactions, planning and organizing diverse learning activities to actively engage students, collaborating with colleagues, and reflecting on their teaching practices. However, notable differences emerged, particularly in terms of providing choices and scaffolding. Finnish teachers prioritized offering options to enhance democratic classroom environments, while Vietnamese teachers focused more on providing support to students with lower proficiency levels. Finally, Vietnamese teachers encountered more challenges compared to Finnish teachers and expressed a need for in-service training to enhance their teaching competencies. The study provides suggestions for teachers and other stakeholders to enhance student participation within school contexts.
Keywords: Participation, multidisciplinary modules, Finnish teachers, Vietnamese teacher, elementary education